PROGNOSTICATION OF VACCINATION EFFICACY - N.F. Snegova; S.M. Kharit; V.K. Tatochenko; M.P. Kostinov (Union of pediatricians of Russia, 2010)
The article focuses on the study of protective immunity in vaccination with pneumococcal conjugated 7-valent vaccine (PCV7) against related vaccine serotypes. It provides results of a study which compared the opsonization capability of all vaccine serotypes with that of two related serotypes (6A and 19A) to analyse immune response. The study results showed that functional cross immunity to serotype 19A after vaccination with conjugated vaccine that does not contain polysaccharide of this serotype is virtually non-existent. Key words: invasive pneumococcal infections, pneumococcal conjugated 7-valent vaccine, children, related vaccine serotypes, opsonophagocytic activity. (Pediatric Pharmacology. - 2010; 7(2):36-40)